PENGARUH MOTIVASI DAN BIMBINGAN ORANG TUA TERHADAP HASIL BELAJAR PAI SISWA DI SEKOLAH DASAR 02 KOTO NAN IV KECAMATAN RANAH PESISIR - Nurmalinda Nurmalinda; Rosniati Hakim; Rusydi AM (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The field conditions of pupils who lack motivation and parental guidance who frequently do not meet the KKM in Islamic Religious Education subjects are the driving force behind this study. In class V of Islamic Religious Education at State Elementary School 02 Koto Nan IV in the Ranah Pesisir District, this study attempts to determine and comprehend the impact of parental motivation and supervision on learning results. A quantitative research methodology approach is used in this study, and surveys and correlational methods based on the Pearson Product Moment formula were used. Primary data, parental counsel, and secondary data resulting from student learning via PAI are the types of data utilized to encourage learning. The findings from the hypothesis test in this study first demonstrated a significant relationship between the learning motivation variable (X1) and student learning outcomes (Y), with the acquisition of a tcount value greater than ttable at the confidence level = 0.05 and a tcount value = 1.892 > ttable = 1.7341. At the confidence level of 0.05 and with tcount = 1.858 > ttable = 1.7341, the findings of the second hypothesis test demonstrate a significant association between parental supervision (X2) and student learning outcomes (Y). In accordance with the findings of the third hypothesis test, there is a significant association between parental guidance (X2) and student learning outcomes (Y) at a confidence level of = 0.05, specifically with Fcount = 4.364 > Ftable = 3, 59.